Adsorption-Desorption of Hexaconazole in Soils with Respect to Soil Properties, Temperature, and pH - Maznah Zainol; Halimah Muhamad; Ismail Bin Sahid; Idris Abu Seman (Turkish Journal of Agriculture: Food Science and Technology)
The effect of temperature and pH on adsorption-desorption of fungicide hexaconazole was studied in two Malaysian soil types; namely clay loam and sandy loam. The adsorption-desorption experiment was conducted using the batch equilibration technique and the residues of hexaconazole were analysed using the GC-ECD. The results showed that the adsorption-desorption isotherms of hexaconazole can be described with Freundlich equation. The Freundlich sorption coefficient (Kd) values were positively correlated to the clay and organic matter content in the soils. Hexaconazole attained the equilibrium phase within 24 h in both soil types studied. The adsorption coefficient (Kd) values obtained for clay loam soil and sandy loam soil were 2.54 mL/g and 2.27 mL/g, respectively, indicating that hexaconazole was weakly sorbed onto the soils due to the low organic content of the soils. Regarding thermodynamic parameters, the Gibb’s free energy change (ΔG) analysis showed that hexaconazole adsorption onto soil was spontaneous and exothermic, plus it exhibited positive hysteresis. A strong correlation was observed between the adsorption of hexaconazole and pH of the soil solution. However, temperature was found to have no effect on the adsorption of hexaconazole onto the soils; for the range tested.